Research progress on cloud data assured deletion based on cryptography - Jin-bo XIONG; Feng-hua LI; Yan-chao WANG; Jian-feng MA; Zhi-qiang YAO (Tongxin xuebao)
The major challenges faced by the data assured deletion in cloud computing was analyzed,it was observed the main reasons of performing cloud data assured deletion were the characteristics of cloud virtualization and multi-tenancy,as well as the business models of lease and on-demand delivery in cloud computing,and point out three levels of meaning of the cloud data assured deletion.Secondly,the state-of-the-art works on cloud data assured deletion was systematically surveyed from security-oriented view in terms of trusted execution environments,key managements and access control policies.It is also pointed out their highlights,limitations and general problems.Finally,some developing trends of this emerging research field were introduced.